2019
DOI: 10.1111/jpy.12884
|View full text |Cite
|
Sign up to set email alerts
|

Whole community estimates of macroalgal pigment concentration within two southern New Zealand kelp forests1

Abstract: Light availability is a fundamental factor that controls the productivity and distribution of macroalgae and is highly variable, both spatially and temporally, in subtidal coastal systems. Our comprehension of how macroalgae respond to such variability is a significant knowledge gap that limits our understanding of how light influences the structure and productivity of these environments. Here, we examined the pigment characteristics of individual species, and for the first time the whole community, within one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Microscopy showed that diatoms, rather than brown algae, dominated the early stages of settlement at high CO2, and this was confirmed by our pigment analyses after 44 and 72 days of settlement on panels. The pigment composition of brown algae and benthic diatom mats reported in previous studies show that the ratio of Fuc/Chl a in most brown algae (mean values among 30 species: 0.372; Colombo-Pallotta et al, 2006;Desmond et al, 2019;Marambio et al, 2017;Seely et al, 1972;Verma et al, 2017) were lower than those of natural diatom mats (mean values among 4 reports: 1.168; Sundback et al 1996;Wulff et al 2005;2008;Stief et al 2013) (Table S4). Considering the higher ratio of Fuc/Chl a on the panels from the high CO2 site, this confirms that benthic diatoms were dominant at the high CO2 site.…”
Section: Discussionmentioning
confidence: 85%
“…Microscopy showed that diatoms, rather than brown algae, dominated the early stages of settlement at high CO2, and this was confirmed by our pigment analyses after 44 and 72 days of settlement on panels. The pigment composition of brown algae and benthic diatom mats reported in previous studies show that the ratio of Fuc/Chl a in most brown algae (mean values among 30 species: 0.372; Colombo-Pallotta et al, 2006;Desmond et al, 2019;Marambio et al, 2017;Seely et al, 1972;Verma et al, 2017) were lower than those of natural diatom mats (mean values among 4 reports: 1.168; Sundback et al 1996;Wulff et al 2005;2008;Stief et al 2013) (Table S4). Considering the higher ratio of Fuc/Chl a on the panels from the high CO2 site, this confirms that benthic diatoms were dominant at the high CO2 site.…”
Section: Discussionmentioning
confidence: 85%
“…Photosynthetic pigments vary considerably between species, predominantly driven by light availability: when less light is available, more pigments need to be produced to harvest enough energy from scarce photons. For instance, pigments of kelps are generally more concentrated in deeper or more turbid water (Koch et al 2016, Desmond et al 2019) and during darker months (Marins et al 2014, Varela et al 2018. Similarly, brown algal antenna size is larger in species that are distributed lower down on rocky shores and consequently receive less light (Caron et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Pigment concentrations detected in this study were highest for chlorophyll-a at all sites, particularly in basal fronds at BG and JI. Desmond et al (2019) observed that M. pyrifera chlorophyll-a, chlorophyll-c, and fucoxanthin concentrations were invariable at a depth of 2 meters. However, they did note a signi cant increase at depth of 10 meters due to a 64% reduction in light availability.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, pigment synthesis appears to decline with depth, which may indicate that Phaeophycean species are at the limit of their photosynthetic capacity (Desmond et al 2019). Zúñiga et al (2020) found higher chlorophyll-a and chlorophyll-c concentrations in Lessonia spicata than those detected in this study due to higher solar irradiance between December and February.…”
Section: Discussionmentioning
confidence: 99%